Letter to the Editor: A Rare Case of Upper Gastrointestinal Bleeding due to Amyloidosis - Karataş, Ali; Kandemir, Halit; Bilican, Gülden; Cindoruk, Mehmet; Karakan, Tarkan (Turkish Journal of Gastroenterology, 2025)
Cite this article as: Karataş A, Kandemir H, Bilican G, Cindoruk M, Karakan T. Letter to the editor: A rare case of upper gastrointestinal bleeding due to amyloidosis. Turk J Gastroenterol. 2025;36(10):708-710.